Mrp Antiporters Have Important Roles in Diverse Bacteria and Archaea - Ito, Masahiro; Morino, Masato; Krulwich, Terry A. (Frontiers in Microbiology, 2017)
Mrp (Multiple resistance and pH) antiporter was identified as a gene complementing an alkaline-sensitive mutant strain of alkaliphilic Bacillus halodurans C-125 in 1990. At that time, there was no example of a multi-subunit type Na+/H+ antiporter comprising six or seven hydrophobic proteins, and it was newly designated as the monovalent cation: proton antiporter-3 (CPA3) family in the classification of transporters. The Mrp antiporter is broadly distributed among bacteria and archaea, not only in alkaliphiles. Generally, all Mrp subunits, mrpA–G, are required for enzymatic activity. Two exceptions are Mrp from the archaea Methanosarcina acetivorans and the eubacteria Natranaerobius thermophilus, which are reported to sustain Na+/H+ antiport activity with the MrpA subunit alone. Two large subunits of the Mrp antiporter, MrpA and MrpD, are homologous to membrane-embedded subunits of the respiratory chain complex I, NuoL, NuoM, and NuoN, and the small subunit MrpC has homology with NuoK. The functions of the Mrp antiporter include sodium tolerance and pH homeostasis in an alkaline environment, nitrogen fixation in Schizolobium meliloti, bile salt tolerance in Bacillus subtilis and Vibrio cholerae, arsenic oxidation in Agrobacterium tumefaciens, pathogenesis in Pseudomonas aeruginosa and Staphylococcus aureus, and the conversion of energy involved in metabolism and hydrogen production in archaea. In addition, some Mrp antiporters transport K+ and Ca2+ instead of Na+, depending on the environmental conditions. Recently, the molecular structure of the respiratory chain complex I has been elucidated by others, and details of the mechanism by which it transports protons are being clarified. Based on this, several hypotheses concerning the substrate transport mechanism in the Mrp antiporter have been proposed. The MrpA and MrpD subunits, which are homologous to the proton transport subunit of complex I, are involved in the transport of protons and their coupling cations. Herein, we outline other recent findings on the Mrp antiporter.